Analysis of Micro, Small And Medium Enterprises Perception of Financing Channeled by Sharia Peer-to-Peer Lending - Abdul Ramadhani, Alya; Muhammad Ikhsan Harahap; Nurul Inayah (Yayasan Sinergi Kawula Muda, 2025)
This research aims to research and analyze MSME perceptions of financing distributed by Peer To Peer Lending Sharia Lending in Medan City. This research uses a qualitative approach method using primary data through interviews and secondary data obtained from statistical data issued by the Financial Services Authority and Bank Indonesia as well as through literature analysis. The results of this research show that people who carry out sharia fintech financing mostly understand the financing carried out in Sharia Fintech Peer to Peer Lending starting from the product, mechanism and sharia compliance in Peer To Peer Lending Sharia Lending.